Relationship between canopy temperature depression, membrane stability,relative water content and grain yield in bread wheat (Triticum aestivum)under heat-stress environments - GOWDA, D S SAMRAT; SINGH, G P; SINGH, ANJU M (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during winter (rabi) of 2006–08 at New Delhi using 49 diverse wheat (Triticum aestivum L. emend. Fiori & Paol) genotypes and three sowing dates (15 November, 15 December and 5 January) to assess the relationship of physiological parameters with grain yield under hot environment. From the analysis of normal, late and very late sowing date, it is evident that all the characters are showing sufficient amount of variability in all three environments among all the 49 bread wheat genotypes. All the characters expressed significant interaction with environments, indicating that all characters respond to high temperature in different ways in different genotypes. This variability gives sufficient scope for further selection of the traits under consideration. Maximum variation was observed for characters, like canopy temperature depression and membrane injury. Most of the characters had high heritability (broad sense) in pooled analysis. Traits, like canopy temperature depression (at anthesis), canopy temperature depression (10 days after anthesis), membrane injury, had high heritability estimates and can be utilized as selection criteria in stress environments. Grain yield showed positive and significant genotypic correlation coefficients canopy temperature depression at anthesis, canopy temperature depression at 10 days after anthesis and membrane injury per cent. Based on the genotypic coefficient of variation, phenotypic coefficient of variation, genetic advance and heritability, characters canopy temperature depression at anthesis, canopy temperature depression at 10 days after anthesis, membrane injury per cent and relative water content can be used as selection criteria for improving the grain yield in the hot environments.